India's demography : changing demographic scenario in India - Majumdar P K (Rawat, 2013)
This book shows how population growth in India is overwhelmingly linked to death rates mostly caused by epidemics and famines. Once these came under some control, along with the arrival of preventive medicines and improved health care facilities, death rates plummeted rapidly, resulting in faster growth of population. India's Demography recognizes how the control of birth rate and arresting IMR and child mortality became the top priority of India's government to contain population growth. It gives a detailed account of how the general death rate and IMR fell, resulting in an increase in life expectancy, and it also examines some key differentials like sex, education, occupation, religion, and residence. India's 2011 population data confirms that "missing girls" have become a critical issue in age-sex structure in the population. The dismal conditions of health services and education have been emphasized. The impact of economic liberalization, infrastructure development, land use, poor technology for food grain production, per capita consumption/expenditure, employment situation, and many other related issues are thoroughly discussed. The book is critical about some aspects of census operations and reports. Anomalies in age composition of the population, especially in some selected ages, have been highlighted. The drastic drop in the sex ratio in the age group 0-4 during the latter half of the past millennium raises many unanswered questions. In spite of India's Marriage Restraint Act, 1976 and repeated directives from the Supreme Court for making registration compulsory for every marriage, nothing has been done by governments to prevent early marriage of girls.